Karakteristik Sensori Torakur (Tomat Rasa Kurma) Berlapis Tepung Kacang Hijau dengan Perbedaan Suhu dan Lama Pengeringan - Enisya Nur Fawnia Zain; Ita Fatkhur Romadhoni (Kampus Akademik Publiser, 2026)
This study aimed to analyze the sensory characteristics of mung bean flour-coated torakur (date-flavored tomato) under different drying temperatures and drying durations and to determine the best treatment combination based on panelists’ acceptance. The research used an experimental method with a factorial Completely Randomized Design (CRD) consisting of two factors, namely drying temperatures of 60°C and 80°C and drying durations of 3 hours, 4 hours, and 5 hours, resulting in six treatment combinations. Sensory evaluation was conducted using a hedonic test on color, aroma, taste, texture, and overall acceptability by 35 panelists. The data were analyzed descriptively and further tested using Two-Way ANOVA at a 5% significance level, followed by Duncan test when significant differences were found. The results showed that differences in drying temperature and drying duration affected the sensory characteristics of mung bean flour-coated torakur. The treatment at 80°C for 5 hours produced the highest acceptance scores for color, aroma, taste, texture, and overall acceptability. This treatment resulted in an attractive reddish-brown color, a stronger dried-fruit aroma, a sweet taste resembling dates, and a chewy texture preferred by the panelists. Therefore, the combination of 80°C drying temperature and 5 hours drying duration was considered the best treatment for producing mung bean flour-coated torakur.